Apakah Insentif Fiskal Berbasis Kinerja Mendorong Dinamika Pertumbuhan Regional? Bukti Spasial dari Kalimantan Tengah, Indonesia - Sastori Aryanto; Wiwin Zakiah; Benius Benius (PPJP ULM, 2026)
Regional economic disparities remain a persistent challenge in Indonesia's decentralized fiscal system, particularly in resource-rich provinces like Central Kalimantan. This study analyzes the direct influence and spatial spillover effects of Regional Incentive Funds (DID) on regional economic growth and growth dynamics among districts/cities in Central Kalimantan during the 2020–2024 period. Using balanced panel data and the Spatial Durbin Model (SDM) approach, this analysis accommodates spatial dependency through a spatial weighting matrix based on regional proximity. The results indicate significant spatial autocorrelation in regional economic growth and fiscal allocation, as indicated by Moran's I values ​​of 0.214 for economic growth and 0.301 for DID allocation. Empirical findings indicate that DID has a positive and significant direct influence on regional economic growth (0.082; p<0.05), and generates positive spillover effects to neighboring regions (0.054; p<0.05). Furthermore, the growth dynamics model confirms the existence of conditional β growth dynamics, with the initial income coefficient negative and significant (-0.143; p<0.05), indicating that poorer regions tend to grow faster than wealthier regions. This finding indicates that DID functions not only as a governance incentive mechanism but also as a strategic fiscal instrument that promotes spillover-based development and regional growth dynamics. Therefore, policymakers need to integrate spatial aspects into the design of fiscal transfers and strengthen interregional connectivity, infrastructure, and human capital investment to achieve more inclusive regional growth.